REFLEKSI MORALITAS GUGATAN ANAK TERHADAP ORANG TUA DI PENGADILAN DI TINJAU DALAM PERSPEKTIF HUKUM - Suyikati Suyikati (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
ABSTRACT The essence of the relationship between children and parents in Law Number 1 of 1974 on Marriage, article 46 Paragraphs (1) and (2) does not provide legal certainty, considering that there are no articles that explain further about the form of parental care that must be carried out by children, the size of the child's maturity , and the legal consequences if you violate it. So that this regulation cannot run or cannot be fulfilled with certainty. The emergence of the problem of the phenomenon of the rise of lawsuits against parents in court cannot be separated from the decline in morality towards parents regarding the value of children's moral education in formal education and non-formal education in the child's environment, this problem is increasingly unstoppable with the absence of further legal policies as elaboration. Law Number 1 of 1974 concerning Marriage, Article 46 Paragraphs (1) and (2), so that it is clear that the rights of parents are protected and can put the position of parents in what should be desired by these provisions.